RESEARCH ON NONLINEAR VIBRATION CONTROL OF MISSILE STORAGE AND TRANSPORTATION - KANG BingBing; LI HaiJun; DENG Li; ZHU HengHao; ZHAO QingHao (Jixie qiangdu)
In order to reduce the vibration and possible damage in the shipping process,introducing negative stiffness in the vibration isolator,broadening the vibration isolation frequency,reduce the starting vibration isolation frequency,at the same time,proposed a nonlinear speed feedback control method of active control is used to suppress resonance. the research results show that the vibration isolator has good low frequency vibration suppression,high frequency of the vibration isolation effect,it can effectively reduce the vibration harm of missile;Linear velocity feedback combined with cubic velocity feedback can effectively suppress resonance and reduce the effect of non-resonance isolation.